Race, Class, Parenting and Children's Leisure : Children's Leisurescapes and Parenting Cultures in Middle-Class British Indian Families. - Mukherjee, Utsa (Bristol University Press, 2023)
School-age children's everyday lives are changing as they are immersed in digital leisure and organised activities. However, our current understandings of these transitions are race-blind. Presenting the first study of middle-class British Indian families, this book reveals the salience of race and class in shaping parenting cultures and children.
Description based upon print version of record.
Keywords: Play -- Social aspects -- Great Britain.; Recreation -- Social aspects -- Great Britain.; Child rearing -- Great Britain.; East Indians -- Great Britain -- Social life and customs.; Middle class families -- Great Britain.; Jeu -- Aspect social -- Grande-Bretagne.; Éducation des enfants -- Grande-Bretagne.; Indiens (Habitants de l'Inde) -- Grande-Bretagne -- Mœurs et coutumes.; Familles de la classe moyenne -- Grande-Bretagne.; SOCIAL SCIENCE / Social Classes & Economic Disparity.; Child rearing; East Indians -- Social life and customs; Middle class families; Play -- Social aspects; Recreation -- Social aspects; Great Britain; Electronic books.